(untitled) (Journal of Student Affairs in Africa, 2021)
This paper reports on a study done within the Learning Development Unit (LDU) at a South Africanuniversity. It addresses the issue that many students who arrive at university lack the requisite academic skills needed for success in higher education which increases the time taken to graduate. One of the multiple reasons for this is the ‘articulation gap’ between school and higher education in South Africa and in other countries. This articulation gap is exacerbated by the assumption about prior learning on which South Africa’s traditional higher education programmes are based. The purpose of this study is to explore whether learning development interventions can change student attitudes and confidence levels, and develop some of the skills necessary to succeed. The study allows the academic counsellors who provide support a sense of whether their interventions are working. The study was undertaken by analysing student responses to learning development interventions. The data is gleaned from evaluation forms, assessment results and interviews conducted with students over three sets of consultations with each student. There were three hundred students who attended workshops and one hundred who sought individual consultations. Initial analyses suggest that significant gains were made in increasing student coping mechanisms and learning/study skills. This indicates that support offered by the Learning Development Unit develops the capabilities and competencies of academically at-risk learners. It is important to note that the LD unit does not pursue graduate outputs and notions of success rates but focuses on enabling at-risk students, allowing them to engage in more purposeful learning.